193k views
1 vote
Find the length of AG

Find the length of AG-example-1
User Hdsenevi
by
4.5k points

1 Answer

4 votes

Answer:


AG=22

Explanation:

Follow the next steps:


(A-B)/(A-E) =(B-C)/(E-F) =(C-D)/(F-G) =(A-C)/(A-F) =(B-D)/(E-G) =(A-D)/(A-G)

Let:


(A-B)/(A-E) =(B-C)/(E-F)\\ \\(4)/(A-E) =(5)/(10x)\\ \\Solving\hspace{3}for\hspace{3}A-E\\\\A-E=8x

Now:


(C-D)/(F-G) =(A-C)/(A-F) \\\\(2)/(F-G) =(9)/(18x) \\\\Solving\hspace{3}for\hspace{3}F-G\\\\F-G=4x

Hence:


A-G=(A-E)+(E-F)+(F-G)=22x

Finally:


(B-D)/(E-G) =(A-D)/(A-G)\\\\(A-D)/(B-D) =(A-G)/(E-G)\\


(11)/(7) =(22x)/(14x) \\\\(11x^(2) )/(7) -(11)/(7) =0\\\\

Hence:


x=1\\x=-1

Since it would be absurd for
x=-1, the real solution is
x=1

Therefore:


AG=22

User Peralta
by
5.1k points